Galerie Fahnemann : Edition '84. - Prinz, Ursula; Galerie Fahnemann, Berlin (Berlin : Galerie Fahnemann Berlin, 1984)
Bach, Elvira ; Castelli, Luciano ; Chevalier, Peter ; Dornseif, Frank ; Fetting, Rainer ; Hödicke, Karl Horst ; Koenig, Wilmar ; Kummer, Raimund ; Mang, Rainer ; McLean, Bruce ; Penck, A.R. ; Pitz, Hermann ; Pods, Reinhard ; Rohling, Gerd
Duits
Edition '84, Galerie Fahnemann Berlin, 12.07 - 31.08.1984
boek